A side‐effect‐free method of reducing capacitance requirement for modular multilevel converters. (17th November 2021) - Liu, Zhijie; Li, Kejun; Wang, Jinyu; Li, Liangzi
Abstract: In modular multilevel converters (MMCs), the huge capacitor almost takes over half of the cost and weight of a submodule; as a result, the capacitance requirement reduction has attracted wide attention for using smaller capacitors. However, the existing methods have side effects, such as increasing the arm current and adding additional semiconductors, which restrict their practical applications. Thus, a side‐effect‐free capacitance requirement reduction (CRR) method is proposed in this paper. In the method, the capacitor voltage can be decreased by injecting a specific dc signal into the original control system; and the specific dc signal is outputted from the proposed CRR controller according to the transmitted power of the MMC. For ensuring the safe operation, the extent to which the capacitor voltage can be reduced is also studied; and an optimisation model is presented to obtain the minimum allowed capacitor voltage and the safety domain of CRR. The effectiveness of the proposed method is proved by both simulation and experiment. The results show that the capacitance requirement can be reduced by 32.4% without neither increasing the arm current nor adding additional semiconductors.